Cholestasis beyond the Neonatal and Infancy Periods - Khalaf, Racha (Pediatr Gastroenterol Hepatol Nutr, 2016)
Cholestasis results from impairment in the excretion of bile, which may be due to mechanical obstruction of bile flow or impairment of excretion of bile components into the bile canaliculus. When present, cholestasis warrants prompt diagnosis and treatment. The differential diagnosis of cholestasis beyond the neonatal period is broad and includes congenital and acquired etiologies. It is imperative that the clinician differentiates between intrahepatic and extrahepatic origin of cholestasis. Treatment may be supportive or curative and depends on the etiology. Recent literature shows that optimal nutritional and medical support also plays an integral role in the management of pediatric patients with chronic cholestasis. This review will provide a broad overview of the pathophysiology, diagnostic approach, and management of cholestasis beyond the neonatal and infancy periods.